Perio-ortho interdisciplinary management for midline diastema related to abberant frenulum : Manajemen interdisipliner perio-ortho untuk diastema garis tengah yang berhubungan dengan frenulum abberant - Muthmainnah; Asdar Gani; Dian Eka Satya (Makassar Dental Journal, 2023)
The maxillary labial frenulum is often attached to the centre of the upper lip and between the two upper front teeth. Frenectomy is one of the periodontal plastic surgeries to remove high frenulum attachment. This article presents the management of cen-tral diastema correction with labial frenectomy to support successful orthodontic treatment and improve aesthetics. A 25-year-old female wanted to straighten her teeth, found an enlarged central diastema due to a labial frenulum that reached the gingival margin and incisor papillae; there was a high maxillary labial frenulum on the interdental papillae and surrounding tissues. Frenectomy was performed to remove the predisposing factor of periodontal disease due to high frenulum attachment and aimed to correct the central diastema along with orthodontic treatment. The 2-month postoperative control showed that the central diastema had been corrected. It was concluded that frenectomy is one of the periodontal plastic surgeries to remove the highly attached frenulum to achieve a pleasing aesthetic.